An Early Axonopathy in a hLRRK2(R1441G) Transgenic Model of Parkinson Disease - Tagliaferro, Patricia (Neurobiol Dis, 2015)
Mutations in the gene for LRRK2 are the most common cause of familial Parkinson’s disease (PD) and patients with these mutations manifest clinical features that are indistinguishable from those of the more common sporadic form. Thus, investigations of disease mechanisms based on disease-causing LRRK2 mutations can be expected to shed light on the more common sporadic form as well as the inherited form. We have shown that as human BAC transgenic hLRRK2(R1441G) mice age, they exhibit two abnormalities in the nigrostriatal dopaminergic system: an axonopathy and a diminished number of dendrites in the substantia nigra (SN). To better understand disease mechanisms it is useful to determine where in the affected neural system the pathology first begins. We therefore examined the nigrostriatal dopaminergic system in young mice to determine the initial site of pathology. Brains from hLRRK2(R1441G) and littermate control mice at 2–4 months of age were examined by immunohistochemistry, anterograde fluorescent axon labeling and ultrastructural analysis. SN neurons, their projecting axons and the striatal terminal fields were assessed. The first identifiable abnormality in this system is an axonopathy characterized by giant polymorphic axon spheroids, the presence of intra-axonal autophagic vacuoles and intra-axonal myelin invagination. An initial involvement of axons has also been reported for other genetic models of PD. These observations support the concept that axons are involved early in the course of the disease. We suggest that effective neuroprotective approaches will be aimed at preventing axonal degeneration.